Indications of the sedimentary environments by the sedimentary characteristics and trace elements of Ordovician Majiagou Formation, Northern Shaanxi salt basin. Issue 6 (1st November 2020) - Wang, LinLin; Shi, Tao; Chang, Dawei; Zhang, Haitao
ABSTRACT: The abundant geochemical information on elements in the autogenous sedimentary rocks can help reconstruct the paleoenvironment of the stratigraphic sedimentation period. Based on the analysis of sedimentary characteristics of Ordovician Majiagou Formation and the trace elements in limestone, dolomite and gypsum rocks in Northern Shaanxi salt basin, the relationship between the distribution of trace elements of Majiagou Formation and the sedimentary environment is discussed. The results display that Majiagou Formation is mainly composed of the sedimentation of carbonate rocks and evaporites, and the subfacies of open platform and restricted platform are developed. The trace element analysis shows that the deposition period of the Majiagou Formation is dominated by dry hot climate, and there are alternating dry and wet seasons in climate evolution. In middle Ordovician, the sedimentary environment of Majiagou Formation was undergoing the transformation of oxygen enrichment-oxygen deficiency-anoxic environment.